PENGARUH MOTIVASI INTERNAL DAN EKSTERNAL TERHADAP KINERJA KARYAWAN DI PT INTAN PARIWARA KLATEN - Rhisma Dwi Ardiyanti; Alkadri Kusalendra Siharis (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the effect of internal and external motivation on employee performance at PT Intan Pariwara Klaten. This research is a research with a quantitative approach. The research was carried out on PT Intan Pariwara Klaten. Data collection obtained a sample of 91 respondents. The sample selection was carried out randomly by the company through a questionnaire which was analyzed using multiple linear regression. The results showed that the Internal Motivation Variable and External Motivation had a significant partial or simultaneous influence on employee performance of PT Intan Pariwara Klaten. Based on the findings, certain recommendations are described such as: Administration should create a beneficial and profitable workplace so that supervisors have good relationships with employees. Employees will be more attracted to work, if their job is permanent, which will ultimately benefit the organization. Top management should relax company policies and trust employees. Employee dissatisfaction can be eliminated by applying the hygiene factor, so managers should focus on it. Extrinsic motivation makes employees more enthusiastic and enthusiastic so that they are much more effective and productive, which in turn improves workforce performance.